Triphenyl Ether and Triphenyl Amine as Chemical Sensors for Transition Metal Ions Using Electrochemical and Spectroscopic Techniques - Gupta, Shivali (My University, 2021)
This doctoral thesis provides an insight into the synthesis, characterization, and development of triphenyl derivatives for the colorimetric and voltammetric sensing of metal ions and anions. Synthesized molecules were characterized by NMR, mass, and FT-IR spectroscopy. They were studied for their analytical applications as chemical sensors as well as for their biological applications. Naked eye detection of probes has modified their practical application. Experimental results were also compared with results obtained from theoretical calculations using DFT software. Furthermore, detection of amino acids, antibacterial activity, and preparation of molecular logic gate were some of the useful applications of our work. A triphenyl ether derivative having amine linkage (TPEA), 1,1'-((((1,3-phenylene bis (oxy)) bis(2,1-phenylene))bis(azanediyl))bis(methylene))bis(naphthalene-2-ol), was synthesized as a customized receptor for cyanide ions. In the presence of a variety of competitive anions such as HSO4-, H2PO4-, ClO4-, OAc- and halides, TPEA was selective for CN- ions. With a detection limit of 0.4 μM and a binding constant of 4.16x107 M-1, the proposed receptor reacts linearly to CN- ions up to a concentration of 400 μM. The colorimetric response of TPEA towards CN- ions was confirmed by voltammetric technique. TPEA has also been tested as a water-detection probe in acetonitrile. For practical application, paper strips were prepared for naked-eye detection of CN-. A triphenyl ether amide (TPEAM) derivative, N,N'-((1,3-phenylene bis(oxy))bis(2,1- phenylene))bis(2-hydroxy-1-naphthamide), was developed as a probe for electrochemical and optical sensing of copper, cyanide ions and arginine. Among various cations and anions, the ionophore is selective for copper and cyanide ions, with detection limits of 40 nM and 0.4 μM, respectively. Sharp anodic and cathodic peaks in the differential pulse voltammograms of TPEAM-Cu(II) complex suggested a strong ligand ion complexing tendency, which was verified by spectrofluorimetry and 1H NMR titrations. TPEAM-Cu(II) complex also detected arginine, a semi-essential amino acid, in an aqueous medium with a lower detection limit of 4 μM. As potential mechanisms for sensing respective ions, host-guest interactions between TPEAM and Cu(II) ions and intramolecular charge transfer interactions (ICT) for CN- ions have been suggested. The use of TPEAM as a Cu(II) ion probe has also been validated on food samples, with the findings compared to those obtained using atomic absorption spectroscopy. Following the response of TPEAM towards Cu(II) and CN- ions, the molecular logic gate was designed with truth table values. A diimine benzene and naphthaldehyde based molecular architecture (PDI) was synthesized, namely, 1,1'-((1E,1'E)-(1,2-phenylene bis(azanylylidene))bis(methanylylidene)) bis (naphthalene-2-ol), and its sensing behavior was found selective for Al+3 ions with a detection limit of 6.7x10-7 M. The binding event was signaled by the probe forming an absorption band at 406 nm and a new emission band at 504 nm. The mechanism is thought to be the chelation-induced enhanced fluorescence (CHEF) effect and limiting PET phenomena. Electrochemical tests of the probe for Al(III) ions backed up the photophysical results. Probe detected CN- and F- ions selectively using a new absorption band at 412 nm and a “turn-on” fluorescence band at 460 nm, with a detection limit of 1x10-7 M. 1H NMR titrations confirmed the mechanism of anion detection. The experimental results were confirmed using DFT calculations. The presence of water as an impurity in acetonitrile was observed to the degree of 0.4 percent using the PDI-Al(III) complex as a sensor. PDI and its aluminium complex were also tested for antibacterial activity against non-pathogenic E. coli. The successful antibacterial activity of Probe and its aluminium complex was confirmed by fluorescence imaging and SEM analysis.
PhD Thesis
Keywords: Ion sensors; Fluorescence; Voltametry; Optical sensors; DFT Calculations